PENINGKATAN HASIL BELAJAR IPAS MATERI PERUBAHAN ENERGI MENGGUNAKAN MEDIA AUGMENTED REALITY (AR) KELAS III SEKOLAH DASAR - Ratih Ulfa Triana; Budi Lestari; I Ketut Suastika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve students' learning outcomes in Natural and Social Sciences (IPAS) on the topic of energy transformation through the use of Augmented Reality (AR) media for third-grade students at SDN Karangbesuki 3 Malang City in the 2025/2026 academic year. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consisted of planning, action, observation, and reflection stages conducted in two cycles. The research subjects were 28 third-grade students. Data were collected through tests, observations, interviews, and documentation. The research instruments included observation sheets for teacher and student activities, learning outcome assessment tests, interview guidelines, and learning activity documentation. The results showed a continuous improvement in students' learning outcomes in each cycle. Learning mastery increased from 45% in the pre-cycle with an average score of 70, to 64% in Cycle I with an average score of 76, and further increased to 86% in Cycle II with an average score of 83. Based on these findings, it can be concluded that Augmented Reality (AR) media is effective in improving students' learning outcomes in Natural and Social Sciences (IPAS) on the topic of energy transformation for third-grade elementary school students.